ANALYSIS OF IMPLEMENTATION PROGRAM VILLAGE FUNDS IN SUPPORTING REGIONAL REVENUE - Ida Farida (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Implementation is the implementation of a series from activities in order to provide public policy so that the policy can bring the expected results included a series of activities . There are four things that affect  of the process implementation in the program include communications , human resources , executive attitudes , bureaucratic structure . Implementation is directed to activities , actions , or implementation mechanisms not only activity but the activity and to achieve the objectives of the planned activities . Some things to consider in the implementation of the Village Fund is how the efforts of the organizing committee of the Village Fund program to increase community development and community aspirations add facilities in order to increase the role of the community in the village program.